Role Nurse Child to Principle Maintenance Atraumatic in Children - Damayanti, Yusnika; Marpaung, Devi Annisa; Madani, Ultra; Hayati, Sri Mala (PT Inovasi Pratama Internasional, 2024)
Atraumatic care is therapeutic care given to children as the most important intervention in child care to achieve optimal growth and development. optimal care while in the hospital. If a pediatric nurse has a good perception, then the nurse will also have a good attitude and behavior in providing nursing care. The principle of atraumatic care includes 5 components, namely preventing the impact of family separation, increasing the ability of parents to control child care, preventing trauma and reducing pain, not committing violence against children and modifying the physical environment. With the principle of atraumatic care in It is hoped that the child can improve the role of pediatric nurses in implementing the most important interventions in child care in hospitals and can accelerate the healing process and optimize child growth and development.